ANALISIS DIMENSI KOLABORASI SISWA PADA PEMBELAJARAN IPS MATERI KERAJAAN ISLAM DI INDONESIA - Arini Sabila Hikmah; Agung Haryono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education in Indonesia has undergone several curriculum changes, and currently the national curriculum is implemented with an in-depth learning approach. This implementation is expected to transform learning from surface learning into deep learning. One dimension in the in-depth learning approach is the collaborative dimension, previously known as gotong royong (mutual cooperation). This study aims to analyze the application of the collaborative dimension in social studies lessons with the topic of the History of Islamic Kingdoms in Indonesia. This research approach is a qualitative descriptive case study. The research subjects were 7A grade students of Brawijaya Smart School Malang Middle School, who are active and interactive. This study shows that the implementation of the collaborative dimension is running well, with positive support in terms of infrastructure and facilities, and there are obstacles in the form of a lack of student literacy in learning.